Polusi Udara Kendaraan Bermotor Tidak Berpengaruh Terhadap Penyakit ISPA - Sri Neneng Sundari (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Motor Vehicle Pollution Doesn't Affect Against ISPA Disease. Air pollution is a problem that often occurs in the big cities, one of which is in the city of Bandung. Air pollution can cause various diseases from the most important ones namely respiratory, cardiovascular diseases, and to other diseases that attack certain organs. Based on the results of the study, air pollution from the transportation sector reached 60 percents, therefore this study will highlight the impact of motor vehicle air pollution on human’s health in Bandung, especially Acute Respiratory Infections (ARI), because the disease is the 2nd largest of the 20 biggest types of diseases in Community Health Centers / Puskesmas in Bandung. From several air pollutant parameters resulting from vehicle exhaust emissions, SO2 compounds were studied, because SO2 can cause irritation to the respiratory tract. This research using descriptive method, it can be concluded that air pollution caused by vehicle exhaust emission gas doesn’t directly affect the occurrence of Acute Respiratory Infections (ARI) in Bandung. The disease can occur due to other factors not examined in this paper, due to indoor air pollution, cigarette smoke pollution, industrial pollution or the continued use of synthetic chemicals.